2017
DOI: 10.1371/journal.pone.0171975
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cardiac effects of exogenous angiotensin 1-7 in rats with subtotal nephrectomy are prevented by ACE inhibition

Abstract: We previously reported that exogenous angiotensin (Ang) 1–7 has adverse cardiac effects in experimental kidney failure due to its action to increase cardiac angiotensin converting enzyme (ACE) activity. This study investigated if the addition of an ACE inhibitor (ACEi) to Ang 1–7 infusion would unmask any beneficial effects of Ang 1–7 on the heart in experimental kidney failure. Male Sprague–Dawley rats underwent subtotal nephrectomy (STNx) and were treated with vehicle, the ACEi ramipril (oral 1mg/kg/day), An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Treatment with ramipril and valsartan resulted in increased plasma Ang I and Ang II and suppression in plasma ACE and ACE2 activity, however, neither monotherapy nor combination therapy affected ACE2 or AT1 receptor expression, both of which remained at levels comparable to non-myocardial infarction control [48]. However, a prior study in the same murine model showed ACE and ACE2 upregulation in the border, infarct zones and in viable myocardium after myocardial infarction, and treatment with ramipril reduced ACE expression while ACE2 remained elevated compared to non-infarcted control [49]. A recent study in the same murine model demonstrated that treatment with olmesartan or telmisartan increased both cardiac ACE2 mRNA and protein expression while augmenting plasma Ang 1-7/Ang II ratios resulting in improved cardiac function and alleviated collagen disposition [40].…”
Section: Ace2 Regulation and Cardiovascular Diseasementioning
confidence: 78%
“…Treatment with ramipril and valsartan resulted in increased plasma Ang I and Ang II and suppression in plasma ACE and ACE2 activity, however, neither monotherapy nor combination therapy affected ACE2 or AT1 receptor expression, both of which remained at levels comparable to non-myocardial infarction control [48]. However, a prior study in the same murine model showed ACE and ACE2 upregulation in the border, infarct zones and in viable myocardium after myocardial infarction, and treatment with ramipril reduced ACE expression while ACE2 remained elevated compared to non-infarcted control [49]. A recent study in the same murine model demonstrated that treatment with olmesartan or telmisartan increased both cardiac ACE2 mRNA and protein expression while augmenting plasma Ang 1-7/Ang II ratios resulting in improved cardiac function and alleviated collagen disposition [40].…”
Section: Ace2 Regulation and Cardiovascular Diseasementioning
confidence: 78%
“… Male Wistar rats/ Doxorubicin-induced cardiomyopathy model No change in cardiac ACE2 protein expression in doxorubicin treated rats H. Ma et al (2017) Ramipril/ ACE-Inh. Male Sprague Dawley rats/ Subtotal nephrectomy induced kidney disease model No effect on cardiac ACE2 activity in subtotal nephrectomized rats Burrell, Gayed, Griggs, Patel, & Velkoska (2017) Captopril/ ACE-Inh. Female Wistar rats/ Ovariectomized rat model for osteoporosis Increased bone ACE2 protein expression in osteoporotic rats.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…However, in other experiments, myocardial fibrosis on histology was first detected at 5 weeks (mortality unknown) [78]. Similarly, myocardial fibrosis can also be induced after 10 days of right nephrectomy, which is consistent with an increase in collagen content [74]. But Chang et al observed only impaired cardiac relaxation without myocardial fibrosis 8 weeks after left nephrectomy [79].…”
Section: Unilateral Nephrectomy Modelmentioning
confidence: 83%
“…Nephrectomy causes water and sodium excretion disorders, resulting in increased blood volume, extracellular fluid volume, ventricular pressure, and volume overload; this ultimately leads to cardiac disease. Activation of RASS system [74] and parasympathetic disorder [75] are considered to be the pathogenic factors of nephropathy and its cardiovascular complications. e 5/6 nephrectomy model is considered a classic model for studying cardiovascular complications of kidney disease.…”
Section: Unilateral Nephrectomy Modelmentioning
confidence: 99%